When the levees broke a requiem in four acts ; a human tragedy ; an HBO documentary films event - Blanchard, Terence 1962- (Home Box Office, 2006)
Four acts document distinct perspectives on the pivotal events that preceeded and followed Katrina's passage through New Orleans, a catastrophe during which the divide between race and class lines has never been more pronounced.
Aspect ratio 1.78 widescreen
P-Jahr: USA 2006
Enth.: Audio commentary by filmmaker Spike Lee ; Next Movement - Act V: a 105-minute epilogue featuring new interviews and insights that further chronicle the hardship endured by New Orleans in the aftermath of Katrina ; Water is rising: a gallery of photos by David Lee with music by Terence Blanchard
Keywords: Disasters; Environmental degradation; Hurricane Katrina, 2005; Levees; Personal property; Katrina -- Hurrikan; New Orleans, La.; DVD-Video